Delay and Dynamics in Labor Market Adjustment : Simulation Results - Artuc, Erhan (2012)
We simulate numerically a trade model with labor mobility costs added, modeled in such a way as to generate gross flows in excess of net flows. Adjustment to a trade shock can be slow with plausible parameter values. In our base case, the economy moves 95% of the distance to the new steady state in approximately eight years. Gross flows have a large effect on this rate of adjustment and on the normative effects of trade. Announcing and delaying the liberalization can build--or destroy--a constituency for free trade. We study the conditions under which these contrasting outcomes occur.